Sodium-glucose cotransporter-2 (SGLT2) expression in diabetic and non-diabetic failing human cardiomyocytes. (October 2022) - Marfella, Raffaele; Scisciola, Lucia; D'Onofrio, Nunzia; Maiello, Ciro; Trotta, Maria Consiglia; Sardu, Celestino; Panarese, Iacopo; Ferraraccio, Franca; Capuano, Annalisa; Barbieri, Michelangela; Balestrieri, Maria Luisa; Napoli, Claudio; et al.
Abstract: This study aimed at investigating the SGLT2 expression in human cardiomyocytes. Human studies evaluating cardiomyocyte SGLT2s expression are limited. To better clarify this issue, SGLT2 protein expression was assessed in human hearts of diabetic and non-diabetic patients, and in AC16 human cardiomyocyte cell line. A prospective study with a follow-up of patients who underwent their first heart transplant (HTX) was performed. Explanted heart, basal (1 week after HTX), and final (48 weeks after HTX) endomyocardial biopsies (EMBs) from patients were evaluated for SGLT2 occurrence in cardiomyocyte with immunohistochemistry, immunofluorescence and SGLT2 quantization with both real-time reverse transcription-polymerase chain reaction and Western blot analysis. The immunofluorescence co-localization of SGLT2 in cardiomyocyte evidenced that an increased expression in the explanted heart from diabetic patients compared to non-diabetic (p < 0.001). In all final EMBs from diabetic patients, the expression of SGLT2 in cardiomyocyte was increased compared to non-diabetic (p < 0.01). This evidence was confirmed by Western blot analysis of SGLT2 protein. In addition, PCR analysis revealed very low mRNA levels in basal EMBs from diabetic and non-diabetic patients (p = NS), whereas final EMBs from diabetic patients showed higher SGLT2 mRNA levels in diabetic compared to non-diabetic patients (p < 0.05). Cultured human cardiomyocytes exposed to high-glucose showed increased expression of SGLT2 protein compared to cells exposed to normal glucose (p < 0.05). The presence of SGLT2 in cardiomyocytes supports the hypothesis of SGLT2i-mediated impact on metabolic pathways within cardiomyocytes. Moreover, metabolic disorders linked to diabetes may lead promptly to upregulation of SGLT2 levels in human cardiomyocytes. Graphical Abstract: SGLT2 expression in human cardiomyocytes ga1 Highlights: HF affects millions of patients adding a financial burden to global health care systems. SGLT2i reduced cardiovascular mortality in diabetic and nondiabetic patients with HF. SGLT2 is expressed in human cardiomyocytes. SGLT2i cardioprotective effects is linked to direct action on the cardiomyocyte.